Olympism and Corona - Bach, T. (IOC, 2020)
IOC President Thomas Bach today sent a letter to the Olympic Movement entitled "Olympism and Corona" to initiate a comprehensive debate on "the challenges we are facing and the potential of the opportunities we have."